Epidemiology of time-loss injuries in international fencing: a prospective, 5-year analysis of Fédération Internationale d`Escrime competitions - Harmer, P. A. (British Journal of Sports Medicine, 2019)
Objectives The study aimed to determine the risk of time-loss injuries in international fencing and to characterise their type, location, severity and mechanism. Variations in risk associated with sex and discipline categories are also examined.